2020
DOI: 10.3389/fmicb.2020.593217
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Erythromycin-Producing Strain Saccharopolyspora erythraea HOE107 for the Heterologous Production of Polyketide Antibiotics

Abstract: Bacteria of the genus Saccharopolyspora produce important polyketide antibiotics, including erythromycin A (Sac. erythraea) and spinosad (Sac. spinosa). We herein report the development of an industrial erythromycin-producing strain, Sac. erythraea HOE107, into a host for the heterologous expression of polyketide biosynthetic gene clusters (BGCs) from other Saccharopolyspora species and related actinomycetes. To facilitate the integration of natural product BGCs and auxiliary genes beneficial for the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The original BGC of spinosad was heterologously expressed in Sa. erythraea, Streptomyces coelicolor, and S. lividans to obtain the spinosad titer of 1–3 mg/L [ 26 , 27 ]. Metabolic engineering has also be attempted in addition to the replacement of the chassis.…”
Section: Introductionmentioning
confidence: 99%
“…The original BGC of spinosad was heterologously expressed in Sa. erythraea, Streptomyces coelicolor, and S. lividans to obtain the spinosad titer of 1–3 mg/L [ 26 , 27 ]. Metabolic engineering has also be attempted in addition to the replacement of the chassis.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, fifteen Actinobacteria strains, among which there are 11 Streptomyces spp., have been co-cultivated in two different media and a large number of differences have been observed as a consequence of the effect of VCs from the companion organism: differences in sporulation, activation of silenced pathways, increased production of compounds, etc. Although not all of these Actinobacteria were isolated from the same niche, they are phylogenetically related and all of them present enormous metabolic potential [ 18 , 19 , 73 76 ]. However, the results have not shown any new unknown compounds.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that there should be some unknown regulator(s) likely present only in Pseudonocardia species, which may play a critical regulatory role in NPP biosynthesis. Further research needs to be pursued to identify in more detail the relationship between global regulatory network and NPP-BAC clone expression in a rare actinomycetes like P. autotrophica [ 27 , 28 ]. In addition, more comparative and systematic studies should be conducted to find out why NPP B1 production was not observed when pNPPB1s or pNPPB1s+pNPPREG was expressed in heterologous hosts such as S. coelicolor and S. lividans (data not shown).…”
Section: Discussionmentioning
confidence: 99%